2009
DOI: 10.1136/vr.164.10.304
|View full text |Cite
|
Sign up to set email alerts
|

Probable zoonotic transmission of verocytotoxigenic Escherichia coli O157 by dogs

Abstract: VEROCYTOTOXIGENIC Escherichia coli (VTEC) of serogroup O157 is an important pathogen of human beings, with potentially serious consequences, including the development of haemolytic uraemic syndrome (Mainil and Daube 2005). It has been isolated from many animal species, but ruminants, especially cattle, are considered to be the main reservoirs of infection (Caprioli and others 2005). Contact with the farming environment, and direct and indirect contact with animals other than domestic pets are risk factors that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…The importance of companion animals (pets) in the epidemiology of STEC infection should not be underestimated. Via their feces, pets, such as dogs and cats can serve as asymptomatic shedders in the epidemiology of a wide range of STEC serotypes (Beutin, 1999;Roopnarine et al, 2007;Hogg et al, 2009;Rumi et al, 2012). Accordingly, several clinical infections due to canine and feline exposure have been reported (Busch et al, 2007;Persad and LeJeune, 2014;McFarland et al, 2017).…”
Section: Domestic Animals Are Indisputable Reservoirs Of Stecmentioning
confidence: 99%
“…The importance of companion animals (pets) in the epidemiology of STEC infection should not be underestimated. Via their feces, pets, such as dogs and cats can serve as asymptomatic shedders in the epidemiology of a wide range of STEC serotypes (Beutin, 1999;Roopnarine et al, 2007;Hogg et al, 2009;Rumi et al, 2012). Accordingly, several clinical infections due to canine and feline exposure have been reported (Busch et al, 2007;Persad and LeJeune, 2014;McFarland et al, 2017).…”
Section: Domestic Animals Are Indisputable Reservoirs Of Stecmentioning
confidence: 99%
“…It has been suggested that dogs may acquire STEC O157:H7 from foods which might be contaminated with E. coli O157:H7 or from ruminants which are considered to be the principal reservoirs of the organism (Hogg et al, 2009;Ojo et al, 2010). Besides, dogs might wander from home and have direct access to slaughter-houses and meat markets where they scavenge for remnants of fresh meat (Adeyemo, 2002).…”
Section: Esherichia Coli O157:h7 Isolationmentioning
confidence: 99%
“…Cattle can be considered as reservoir of the serotype O157:H7 and transmit the infection to the human and dogs mainly by oral-fecal route, including contaminated raw milk and meat, dogs are the source of human infection with pathogenic E. coli O157: H7. and the infection of dogs is acquired from ruminants that are a storehouse of these bacteria, and the method of transmission is through direct contact between humans and pets animals as well as fecal and urine contamination (4,5). The previous studies have been performed to identify and isolate E. coli O157:H7 in dogs.…”
Section: Introductionmentioning
confidence: 99%